Analysis of The Development of Food Crop Commodities in East Kolaka District - intan ayu permata sari; La Ode Alwi; Dhian Herdhiansyah (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This research aims to determine the development of food crop commodities in East Kolaka Regency. The method used is a descriptive method by presenting a complete picture of the development of food commodities in East Kolaka Regency. The food crops commodities in East Kolaka Regency are rice, corn, green beans, cassava, sweet potatoes, and peanuts. The area of agricultural land in East Kolaka Regency is 364,462 ha or 91.07% and the largest food crop commodity is 27,421 ha of lowland rice, 6,518 ha of maize, 237 ha of cassava, 75 ha of sweet potato. commodity peanuts covering an area of 71 ha, and commodity mung bean covering an area of 13 ha. The food crop commodity of East Kolaka Regency, the level of productivity of the rice commodity was 127,539 tons, and the largest land area compared to other commodities was 27,421 ha. The commodity for maize includes the second level of production and productivity of rice, namely 16,536 tons, then 695 tons of cassava, 72 tons of sweet potato, 43 tons of peanuts, and 17 tons of green beans.